(untitled) (American Journal of Innovation in Science and Engineering, 2023)
In Nigeria today, there is a lot of waste that is being generated on a daily basis. From Domestic wastes to kitchen wastes, poultry and livestock not excluded. Due to the current energy crisis and climate change, the country could benefit greatly from an alternative energy source which is eco-friendly, renewable, sustainable and efficient. This alternative energy source is called ‘’Biogas”. Biogas is formed by anaerobic digestion of organic materials. Biogas can be produced from kitchen wastes, cow dungs, poultry, pig faeces, etc. These wastes from the Bio-digester can later be treated as a by-product to give a nutrient rich organic fertilizer that can be used in farmlands and gardens. This paper outlines the benefits of organic waste and its potentials for domestic as well as industrial use when compared to other conventional fuels. The selected organic wastes that were thoroughly analyzed in this research work are; Human excreta, Pig excreta, sheep and goat excreta, abattoir waste, poultry excreta, cattle excreta, crop residue and municipal waste. Using computational techniques based on standard measurement. It was deduced that Nigeria generates about 591 million tons of the selected organic waste per annum. The results obtained from the research work shows that biogas has the potential of yielding about 32.29 billion m3 of biogas equivalent to 178 894 587.6 MWh. This estimated biogas yield will completely displace use of kerosene and coal for domestic cooking hereby reducing the consumption of wood fuel by 70%. The research also gives a recommendation for government and also the NGOs to encourage waste to energy mobilization and support its implementation in rural areas of the country.